Attribute table, evaluation data & analysis of evaluation data for published paper "Obligations and aspirations: a critical evaluation of offshore wind farm cumulative impact assessments" - Willsteed, Edward A.; Jude, Simon; Gill, Andrew B.; Birchenough, Silvana N. R. (Cranfield University, 2017)
Files uploaded enable: 1) application of the critical evaluation framework developed to other fields; 2) re-examination of the data generated by the evaluation. The full methodology is reported in the published paper. Information identifying individual Environmental Statements has been removed from publicly available data.
Keywords: Marine renewable energy; Offshore Wind Farms; Cumulative effects; Cumulative impact assessment; Cumulative effects assessment; Environmental impact assessment; Marine spatial planning; Ecology; Conservation and Biodiversity; Biological Oceanography; Environmental Management